Latihan pangkalan data atas talian JSTOR, 18 February 2016 - Universiti Malaysia Sarawak, Centre for Academic Information Services (Centre for Academic Information Services (CAIS), 2016)
Training session on the electronic resources JSTOR has been held on 18th February 2016, 10.00 am at Santubong computer lab, Level G CAIS. JSTOR (short for Journal Storage) is an online system for archiving academic journals, founded in 1995. It provides its member institutions full-text searches of digitized back issues of several hundred well-known journals. Used by millions for research, teaching and learning. With more than a thousand academic journals and over 1 million images, letters and other primary sources, JSTOR is one of the world's most trusted sources for academic content. The training session has been conducted by Mr. Jaideep Gurwara (Director Globe Publication PVT. LTD.)